2017
DOI: 10.3390/cli5020033
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Rainfall Warnings Based on the TOPSIS Method

Abstract: Abstract:Extreme weather, by definition, is any unexpected, unusual, unpredictable, severe or unseasonal weather condition. A rainfall event that is considered normal in one region may be considered a torrent in a dry region and may cause flash flooding. Therefore, appropriate weather warnings need to be issued with respect to areas with different climates. Additionally, these alerts should be easy to understand-by clear classification-in order to apply reinforcements. Early warning levels not only depend on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The best alternative is identified as the closest to the positive ideal solution and the farthest from the negative ideal solution. The TOPSIS method is widely used for ranking alternatives and for decision making in water resources management, early warning systems, participatory flood risk management, social learning, and consensus achievement among stakeholders [32][33][34][35]. It has been increasingly used in the last decade in the field of climatology to select among different datasets [24][25][26][27][28]36].…”
Section: Ranking and Selection Of Rcmsmentioning
confidence: 99%
“…The best alternative is identified as the closest to the positive ideal solution and the farthest from the negative ideal solution. The TOPSIS method is widely used for ranking alternatives and for decision making in water resources management, early warning systems, participatory flood risk management, social learning, and consensus achievement among stakeholders [32][33][34][35]. It has been increasingly used in the last decade in the field of climatology to select among different datasets [24][25][26][27][28]36].…”
Section: Ranking and Selection Of Rcmsmentioning
confidence: 99%
“…Differences in the extent of atmospheric precipitation in Poland are primarily explained by the effect of certain types of atmospheric circulation; high importance is attributed to cloud cover (Degirmendžić, Kożuchowski and Żmudzka 2004;Żmudzka 2009;Twardosz, Niedźwiedź and Łupikasza 2011;Młyński, Cebulska and Wałęgaet 2018). For extreme phenomena it is difficult to prove the significance of a trend and regularities in the development of a given phenomenon (Pfeifer et al 2015;Zeyaeyan et al 2017). The observed differences in temporal distribution of precipitation totals between particular years result in irregular periods of drought and excessive precipitation, whose negative social and economic effects cannot be prevented (Kundzewicz, Radziejewski and Pińskwar 2006;Dumrul and Kilicarslan 2017;Brázdil et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…TOPSIS 32 , a multi-criteria decision-making method has been successfully implemented in various studies, and the results have revealed its great potential as an MADM method (e.g., 33,34 ). After simulating the generated scenarios and calculating the values of the five evaluation indicators, TOPSIS was used to rank the scenarios and select the best one.…”
Section: Topsismentioning
confidence: 99%